2020
DOI: 10.31234/osf.io/wncb5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Shift-of-Strategy (SoS) approach: Using evidence strategically to influence suspects’ counter-interrogation strategies

Abstract: Objective: The Shift-of-Strategy (SoS) approach is an extension of the Strategic Use of Evidence technique. In the SoS approach, interviewers influence suspects’ strategies to encourage suspects to become more forthcoming with information by challenging discrepancies between their statements and the available evidence, in a non-accusatory manner. Our aim was to test the effectiveness of two variations of the SoS approach, one in which the interviewer responded immediately to any discrepancies with the evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
3
3
0
Order By: Relevance
“…Inconsistent with Scharff's technique, however, the Army Field Manual's "we know all" approach is compatible with approaches that involve accusatory pressure (see, e.g., Duke et al, 2018), and unlike Scharff's use of claims and avoidance of direct inquiry, the approach can entail "interjecting pertinent questions" when the source begins to provide new information. In contrast, the hypothesized underpinnings of the Scharffian illusion of knowing it all are similar to and consistent with the theoretical conceptualization behind the Strategic Use of Evidence (SUE) technique of interviewing and its extensions, which aim to influence interviewees' behavior in part by controlling their perception of how much the interviewer knows (see, e.g., Luke & Granhag, 2020). These theoretical similarities exist despite superficial differences between Scharff's technique, which emphasizes demonstration of knowledge, and the SUE technique, some of the tactics of which emphasize not demonstrating knowledge (Granhag & Hartwig, 2015).…”
Section: Scharff's Methods Of Interrogationsupporting
confidence: 61%
“…Inconsistent with Scharff's technique, however, the Army Field Manual's "we know all" approach is compatible with approaches that involve accusatory pressure (see, e.g., Duke et al, 2018), and unlike Scharff's use of claims and avoidance of direct inquiry, the approach can entail "interjecting pertinent questions" when the source begins to provide new information. In contrast, the hypothesized underpinnings of the Scharffian illusion of knowing it all are similar to and consistent with the theoretical conceptualization behind the Strategic Use of Evidence (SUE) technique of interviewing and its extensions, which aim to influence interviewees' behavior in part by controlling their perception of how much the interviewer knows (see, e.g., Luke & Granhag, 2020). These theoretical similarities exist despite superficial differences between Scharff's technique, which emphasizes demonstration of knowledge, and the SUE technique, some of the tactics of which emphasize not demonstrating knowledge (Granhag & Hartwig, 2015).…”
Section: Scharff's Methods Of Interrogationsupporting
confidence: 61%
“…Inconsistent with Scharff's technique, however, the Army Field Manual's “we know all” approach is compatible with approaches that involve accusatory pressure (see e.g., Duke, Wood, Magee, & Escobar, 2018), and unlike Scharff's use of claims and avoidance of direct inquiry, the approach can entail “interjecting pertinent questions” when the source begins to provide new information. In contrast, the hypothesized underpinnings of the Scharffian illusion of knowing it all are similar to and consistent with the theoretical conceptualization behind the strategic use of evidence (SUE) technique of interviewing and its extensions, which aim to influence interviewees' behavior in part by controlling their perception of how much the interviewer knows (see e.g., Luke & Granhag, 2020). These theoretical similarities exist despite superficial differences between Scharff's technique, which emphasizes demonstration of knowledge, and the SUE technique, some of the tactics of which emphasize not demonstrating knowledge (Granhag & Hartwig, 2015).…”
Section: Introductionsupporting
confidence: 63%
“…Following the same principles, substantial intra-individual correlations of information disclosure decisions may lead to bimodal or multimodal distributions of the proportion of disclosed information. Indeed, previous research on interviewing, including the present preliminary study, has repeatedly observed bimodal distributions of information disclosure (e.g., Brimbal & Luke, 2019;Luke & Granhag, 2020;Luke et al, 2014;Srivatsav et al, 2019).…”
Section: Figure 2 Information Disclosure In the Preliminary Studysupporting
confidence: 55%
“…Previous research has rarely explicitly addressed individual differences in the propensity to disclose information or in the sensitivity to costs and benefits of disclosure. The past research that provides data on this issue, as well as the present preliminary study, suggests that there are substantial individual differences, such that people's decisions to disclose one piece of information are correlated with their decision to disclose other pieces (see e.g., Luke & Granhag, 2020). Considering this correlated structure of hypothetical data leads to useful insights concerning the distributions of disclosed information.…”
Section: Figure 2 Information Disclosure In the Preliminary Studymentioning
confidence: 57%